The craft of theology : from symbol to system - Dulles, Avery, 1918-2008. (New York : Crossroad, 1995)
Illustrates how a "post-critical" theology can draw on the riches of scripture and tradition as it reflects on the faith of the church in new contexts.
Includes bibliographical references (p. 225-251) and index.
Keywords: Theology; Catholic Church -- Doctrines